Establishing Semantic Network of the Malaysian Affordable Housing Livability Dimensions. International Journal of Real Estate Studies - Wilson Rangga, Anthony Jiram; Fauziah, Raji; Fatin, Aziz; Ibrahim, Sipan (Penerbit UTM Press, 2019)
The impetus for the study is the growing awareness of the deterioration of livability, particularly in urban environments due to the pressure of imbalance development pattern. An investigation into the views of industry and academia revealed there is a considerable gap in determining the perimeter that predicting the livability of affordable housing scheme in Malaysia. This paper offers the qualitative exploration of the Malaysian affordable housing livability dimensions. The purpose of this case study design study is to explore participant’s views consisting government bodies, public and private universities, and non-governmental organizations with the intent of using this information to develop the conceptual framework of affordable housing livability. This was accomplished by collecting the focus group data to provide a full picture of the extent of coverage of affordable housing livability dimensions. Findings from this qualitative phase will be used to test the dimensions with the sample of affordable housings’ residents. The study reveals that the affordable housing livability is conceptualized as a composite of seven dimensions. Further validation for the derivation of affordable housing livability construct validity is needed to provide adequate exploration. This study contributes to the existing body of knowledge in livability studies in terms of dimension construct. Conclusively, the findings can help researchers, planners, policy makers and others in the formulation of housing criteria guidelines for the introducing of livable housing as part of the effort to incorporate these features into any new housing projects, to improve the quality of life of in urban environments.